Antifungal analysis of incorporation of the essential oil of Cymbopogon citratus (D.C.) Stapf into polymethyl methacrylate - Ronaldo Campêlo dos SANTOS; Manuela Gouvêa Campêlo dos SANTOS; Thiago Franco de Oliveira CARNEIRO; Flávia Lucisano Botelho do AMARAL (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Objective: Evaluated the antifungal effect of the incorporation of different concentrations of the essential oil Cymbopogon citratus (capim santo), into polymethylmethacrylate (PMMA) against Candida albicans. Methods: Fifty specimens were fabricated and divided into five groups: Group 1, PMMA + 10% essential oil (n=10); Group 2, PMMA + 15% essential oil (n=10); Group 3, PMMA + 20% essential oil (n=10); Group 4, PMMA + 25% essential oil (n=10); Group 5, PMMA (n=10). PMMA powder was mixed with the monomer and the mixture was placed in disc-shaped cavities measuring 15 mm in diameter, 2 mm thick. To evaluate the antifungal activity of the experimental specimens, the standard strain of Candida albicans was tested. After incubation, the colony count of each plate was performed using a digital colony counter, obtaining the number of colony forming units (CFU) and the Kruskal-Wallis test was applied. Results: There was statistically significant difference in the CFU count of Candida albicans as a consequence of the addition of Cymbopogon citratus essential oil to PMMA (p < 0.001) and values were significantly higher in comparison with those of all the other groups, when the essential oil was incorporated as incorporated into the PMMA in the concentration of 20%. In the other concentrations, no difference in values was observed in comparison with the Control Group without essential oil of Cymbopogon citratus. Conclusion: The acrylic resin with the essential oil incorporated into it in different concentrations provided no effect against development of the genus Candida.